Delivering Bundled Gender Sensitive Livestock Climate Information Services - CGIAR Research Initiative on Livestock and Climate; International Livestock Research Institute (International Livestock Research Institute, 2025)
The CGIAR Research Initiative on Livestock and Climate aimed to address livestock system climate adaptation and mitigation through five interrelated work packages. This series of Work Package Results Fact Sheets details our key outcome results. Between 2022 and 2024, Work Package 2 (WP2) responded to the critical challenges faced by livestock systems in low- and middle-income countries, notably vulnerability to climate hazards such as drought, climate variability and extreme weather events. Because livestock production is essential for poverty reduction, nutrition security and sustainable livelihoods, and because it is highly vulnerable to climate risks, WP2 developed and scaled integrated climate-related service interventions to enhance climate risk management. Our approach was to deliver tailored and gender-sensitive climate information services, participatory agro-climate advisories, innovative financial products (insurance and climate- linked credit) and digital market intelligence tools.